PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS SISWA PADA MATERI LOGIKA MATEMATIKA KELAS XI PH 1 - Fadhila Febriliana; Aflich Yusnita Fitrianna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this survey is the use of problem based learning to increase students' mathematical understanding on the material of logika matematika in class. The population in this survey is students in SMK Negeri 3 Cimahi. The sample of this survey is the students from class XI PH 1 as many as 35 students. This survey application the classroom action research strategy from Kemmis and Taggart which comprises of pre-cycle, cycle I, cycle II and cycle III. It is completed in 4 phase, namely planning, implementation, observation and reflection. This survey instrument uses a written test to obtain data on improving students' mathematical understanding abilities. The survey procedure was done by drawing conclusions from the average mathematical understanding ability of students and the percentage of students' mastery with the provisions of the KKM score of 75. The results obtained that the average mathematical understanding ability of students in the pre-cycle was 45 with a complete presentation by 0%, in the cycle. Cycle I improved to 79 with a complete presentation by 69%, in the second cycle it improved again to 87 with a complete presentation by 91% and in the third cycle it improved again to 89 with complete presentation by 94%.